Conferred with a new life: A case report of management of a severe midface trauma and subsequent oral rehabilitation. Issue 8 (25th August 2021) - Pournabi, Alireza; Moslemi, Hamidreza; Shafiei, Shervin; Dastgir, Ramtin; Abbasi, Kamyar; Alam, Mostafa
Abstract: Maxillofacial traumas have been associated with 14%‐17% of all facial injuries. The most common etiology of mid‐facial traumas is motor vehicle accidents followed by interpersonal assaults. The devastating nature of maxillofacial defects makes reconstruction of the midface challenging, due to multiple required surgeries and extensive rehabilitation phase. The midface has been defined as the area between the zygomaticofrontal sutures and the maxillary occlusal plane. Midface traumas are significantly more challenging to manage compared to isolated facial since there is limited intact and unharmed framework to guide with anatomic reductions. Therefore, the appropriate surgical approach to a maxillofacial trauma must follow a systematic scheme. Besides, one of the main consequences of maxillofacial traumas is destruction of the teeth and teeth bearing alveolar bone. Oral rehabilitation utilizing dental implants of these patients must be considered to provide the higher quality of life. Here, we report the management and further oral rehabilitation of a case suffering severe midface trauma following a motor vehicle accident where the patient was hit by a lorry. Abstract : In this study, we reported the management and further oral rehabilitation of a case suffering severe midface trauma. This study emphasizes on the crucial role of a well‐managed surgery and its subsequent improvement in patient's quality of life.